Critical-current suppression in sub-micron intrinsic Josephson junction arrays - Fenton, J; Korsah, M; Grovenor, C; Warburton, P (2006)
We present experimental results on intrinsic Josephson junctions fabricated by three-dimensional gallium focussed-ion-beam (FIB) milling in c-axis-oriented Tl2Ba2CaCu2O8 thin films. We report measurements of the dependence of the switching current density of these arrays at 4.2 K upon the junction cross-sectional area A showing strong suppression of the switching current density for junctions with A 1 νm2; the switching current extrapolates to zero for A ∼ 0.25 νm2. We discuss the roles of gallium ion implantation and both thermal and quantum fluctuations in this current suppression. We also present in-situ IV measurements demonstrating the use of a liquid-helium-cooled sample stage in conjunction with the FIB milling. © 2006 IOP Publishing Ltd.